Pembelajaran Menyimak Apresiatif Cerpen dengan Metode Story Telling di Kurikulum Merdeka Belajar - Rahman, Ainur; Albaburrahim (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
The purpose of this research is to improve the learning of short story appreciative listening by using the storytelling method, especially in the era of independent learning. The short story taken is Kartini's short story by Putu Wijaya. This research uses descriptive qualitative method. The source of the data for this research is SMP NU Sumenep. Data were collected through observations, field notes, and documentation. Data analysis by collaborating data with the learning method used. The results showed that the storytelling method was effective in improving appreciative listening learning, especially to support the curriculum.